The clinical study of the advantages of quartz intrachannel posts to the life extension of the teeth with extensive destruction of the crown part (Эндодонтия Today)
The evaluation time ranges from 6 months to 2 years and 47 patients were examined. The material comprised 97 teeth restored with 156 quartz fiber posts. We did final postendodontic restoration after sanation or after we noticed positive dynamics. Patients were from 18 to 71 years old. All the teeth were previously endodontically treated with vertical condensation of warm gutta-percha and eugenol-free sealer. 62 treated teeth were restored with one post, 20 teeth had two posts, 15 teeth had three posts, and only 9 teeth with oval-shaped canals were restored with the accessory posts. In observation time we didn’t find out any complications, discoloration of teeth, debonding and fractures of posts.